2010
DOI: 10.1002/marc.201000266
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Poly(Pt‐salphen)‐(p‐phenyleneethynylene) as Phosphorescent Conjugated Linear‐Rod and Coilable Sensory Materials

Abstract: Phosphorescent conjugated polymers consisting of alternating p-phenylene-ethynylene and 'para-' or 'meta-type' Pt(II)-salphen luminophore units have been synthesized. Side-arms bearing different substituents (n-alkoxy and acetylated-sugar) have afforded contrasting emission properties that are attributed to the polymer conformation, extent of π-stacking interactions and differences in chemical structure. Intriguing selectivity in luminescent sensing of metal ions has been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, by the variation of the substitution pattern of the halogens at the salphen units, helical or zig-zag-type polysalphen chains with Zn 2þ , Ni 2þ , and Cu 2þ 104b as well as with Pt 2þ centers have been realized. 105 Furthermore, different external substituents like saccharines were used as well. 105,106 An interesting example of a 1D salphen polymer with an ordered 3D structure was presented by Liu and coworkers in 2015 by condensing a bissalicylaldehyde and phenazine diamine with zinc acetate.…”
Section: D-salen and Salphen Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, by the variation of the substitution pattern of the halogens at the salphen units, helical or zig-zag-type polysalphen chains with Zn 2þ , Ni 2þ , and Cu 2þ 104b as well as with Pt 2þ centers have been realized. 105 Furthermore, different external substituents like saccharines were used as well. 105,106 An interesting example of a 1D salphen polymer with an ordered 3D structure was presented by Liu and coworkers in 2015 by condensing a bissalicylaldehyde and phenazine diamine with zinc acetate.…”
Section: D-salen and Salphen Polymersmentioning
confidence: 99%
“…105 Furthermore, different external substituents like saccharines were used as well. 105,106 An interesting example of a 1D salphen polymer with an ordered 3D structure was presented by Liu and coworkers in 2015 by condensing a bissalicylaldehyde and phenazine diamine with zinc acetate. 107 It is suggested that due to the extended aromatic backbone of the precursors, the resulting polymer chains pack in an ordered fashion to form crystalline supramolecular 3D networks.…”
Section: D-salen and Salphen Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory materials that can selectively detect Cu 2+ ions are of interest,12 but reports about phosphorescent Cu 2+ sensors are few. A series of conjugated polymers composed of alternating p ‐phenylene‐ethynylene and “para‐” ( p ‐ P2 and p ‐ P3 ) or “meta‐type” ( m ‐ P2 and m ‐ P3 ) Pt(II)‐ salphen complex units was synthesized by Chan et al13 The side‐arms bearing acetylated‐sugar afforded contrasting emission properties that were attributed to differences in the polymer conformation, the extent of π‐stacking interactions and the chemical structure. The luminescent responses of the p ‐ and m ‐ P3 to different metal ions in CH 3 CN indicates the good selectivity to Cu 2+ , which may be assigned to the judicious choice of the side‐arm receptor groups.…”
Section: Design Strategies Of Ptmcs Bearing Optoelectronic Functionsmentioning
confidence: 99%